Effect of leaf remotion on vegetative development and production in cotton - Jácome, Aleksandra Gomes; Soares, José Janduí; Oliveira, Rosa Honorato de; Sobrinho, Francisco Pereira Cordão (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to evaluate the effect of the removal of the leaves of the main stem and of the fruitful branches on the vegetative development and production of cotton (Gossypium hirsutum L.), cultivar CNPA 7H, in greenhouse. According to results, removal of the main leaves reduces the plant height, leaf area, fruit and stem diameter and mainly the production of fruits in the first and second fruiting positions.
Keywords: Gossypium hirsutum; leaf area; stems; plant developmental stages